2015
DOI: 10.1378/chest.14-1368
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hospital Use of Oral Nutritional Supplementation on Length of Stay, Hospital Cost, and 30-Day Readmissions Among Medicare Patients With COPD

Abstract: BACKGROUND: COPD is a leading cause of death and disability in the United States. Patients with COPD are at a high risk of nutritional defi ciency, which is associated with declines in respiratory function, lean body mass and strength, and immune function. Although oral nutritional supplementation (ONS ) has been associated with improvements in some of these domains, the impact of hospital ONS on readmission risk, length of stay (LOS), and cost among hospitalized patients is unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
42
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 49 publications
4
42
1
2
Order By: Relevance
“…Guest et al (2011) (22), in a retrospective analysis of 1,000 homecare adult patients, observed a significant increase in hospital readmission in malnourished patients (BMI < 18.5 kg/m 2 ), with statistical significance (13% vs 5% [p < 0.05]). In an 11-year retrospective study of information on 44 million adult inpatients, Philipson et al found that, relative to patients who did not receive ONS, those given ONS had a shorter average LoS by 2.3 days (95% CI = -2.42 to -2.16), from 10.9 to 8.6 days (21.0% less), and a $4,734 average decrease in episode cost (95% CI = $-4,754 to $-4,714), from an average cost of $21,950 to $17,216 (21.6% decline) (23).…”
Section: Depletion Of Body Muscle and Fat Tissues Including Intra-mentioning
confidence: 99%
“…Guest et al (2011) (22), in a retrospective analysis of 1,000 homecare adult patients, observed a significant increase in hospital readmission in malnourished patients (BMI < 18.5 kg/m 2 ), with statistical significance (13% vs 5% [p < 0.05]). In an 11-year retrospective study of information on 44 million adult inpatients, Philipson et al found that, relative to patients who did not receive ONS, those given ONS had a shorter average LoS by 2.3 days (95% CI = -2.42 to -2.16), from 10.9 to 8.6 days (21.0% less), and a $4,734 average decrease in episode cost (95% CI = $-4,754 to $-4,714), from an average cost of $21,950 to $17,216 (21.6% decline) (23).…”
Section: Depletion Of Body Muscle and Fat Tissues Including Intra-mentioning
confidence: 99%
“…2,19,20 Nutrition screening and interventions (eg, oral nutritional supplements [ONS]) have proven effective for improving patient outcomes and reducing overall costs of care for patients who are malnourished or at risk for malnutrition. [21][22][23][24][25][26][27][28] For example, several studies of hospitalized patients showed that nutrition screening and assessment, when followed by intervention as needed, could shorten length of stay (LOS) by at least 2 days. 24,28,29 Given their integral role during a patient's hospital stay, nurses are ideally positioned to identify patients at risk for malnutrition and facilitate their treatment.…”
mentioning
confidence: 99%
“…[21][22][23][24][25][26][27][28] For example, several studies of hospitalized patients showed that nutrition screening and assessment, when followed by intervention as needed, could shorten length of stay (LOS) by at least 2 days. 24,28,29 Given their integral role during a patient's hospital stay, nurses are ideally positioned to identify patients at risk for malnutrition and facilitate their treatment. [30][31][32] A nurse-led program was initiated at Akron General Medical Center ([AGMC], Akron, Ohio), a Magnet hospital and level 1 trauma center, and a recent addition to the Cleveland Clinic Health System, to update the hospital nutrition care process and streamline its delivery.…”
mentioning
confidence: 99%
“…Patients with advanced COPD often have nutritional deficiency and low body mass index; and long LoS in these patients can be significantly reduced by oral nutrition supplementation [21]. In our LoS patients, we found reduced serum albumin and an increased pressure sore risk as shown by reduced Braden score.…”
Section: Discussionmentioning
confidence: 53%